Hospital-level Variation in Secondary Complications After Surgery. Issue 3 (March 2016) - Wakeam, Elliot; Hyder, Joseph A.; Lipsitz, Stuart R.; Cohen, Mark E.; Orgill, Dennis P.; Zinner, Michael J.; Ko, Cliff Y.; Hall, Bruce L.; Finlayson, Samuel R. G.
Abstract : Objectives: To assess whether hospital rates of secondary complications could serve as a performance benchmark and examine associations with mortality. Background: Failure to rescue (death after postoperative complication) is a challenging target for quality improvement. Secondary complications (complications after a first or "index" complication) are intermediate outcomes in the rescue process that may provide specific improvement targets and give us insight into how rescue fails. Methods: We used American College of Surgeons' National Surgical Quality Improvement Program data (2008–2012) to define hospital rates of secondary complications after 5 common index complications: pneumonia, surgical site infection (SSI), urinary tract infection, transfusion/bleed events, and acute myocardial infarction (MI). Hospitals were divided into quintiles on the basis of risk- and reliability-adjusted rates of secondary complications, and these rates were compared along with mortality. Results: A total of 524, 860 patients were identified undergoing one of the 62 elective, inpatient operations. After index pneumonia, secondary complication rates varied from 57.99% in the highest quintile to 22.93% in the lowest [adjusted odds ratio (OR), 4.64; confidence interval (CI), 3.95–5.45). Wide variation was seen after index SSI (58.98% vs 14.81%; OR, 8.53; CI, 7.41–9.83), urinary tract infection (38.41% vs 8.60%; OR, 7.81; CI, 6.48–9.40), transfusion/bleeding events (27.14% vs 12.88%; OR, 2.54; CI, 2.31–2.81), and acute MI (64.45% vs 23.86%, OR, 6.87; CI, 5.20–9.07). Hospitals in the highest quintile had significantly greater mortality after index pneumonia (10.41% vs 6.20%; OR, 2.17; CI, 1.6–2.94), index MI (18.25% vs 9.65%; OR, 2.67; CI, 1.80–3.94), and index SSI (2.75% vs 0.82%; OR, 3.93; CI, 2.26–6.81). Conclusions: Hospital-level rates of secondary complications (failure to arrest complications) vary widely, are associated with mortality, and may be useful for quality improvement and benchmarking. Abstract : Supplemental Digital Content is available in the text